DOP62 Medication use is increased in the decade prior to IBD diagnosis: A nationwide cohort study. (30th January 2023) - Bonfils, L; Karachalia Sandri, A; Juul Poulsen, G; Agrawal, M; Ward, D J; Jess, T; Colombel, J F; Allin, K H
Abstract: Background: There is increasing evidence of a pre-clinical phase of inflammatory bowel disease (IBD), but its length and progression with time is not well characterized. We here identified the use of any prescription medications within a decade prior to IBD diagnosis and compared their use in a matched population of individuals without IBD. Methods: We harnessed the cross-linked nationwide Danish health registers to identify all individuals with incident IBD in Denmark from 2005 to 2018. Individuals with IBD were matched one to ten to individuals without IBD on age, sex, municipality of residence, and year of IBD diagnosis. Next, we examined their use of any prescription medication within the decade leading to IBD diagnosis or matching date. Prescription histories were compared and examined according to the WHO classification of medication by anatomical main group and therapeutical subgroup. Results: We compared 29, 219 individuals with IBD to 292, 190 individuals without IBD. Up to a decade prior to IBD diagnosis, the IBD population had a significantly higher use of medications across all organ systems than the matched population. Medication use was more abundant in the IBD population at ten years before diagnosis/matching (p-value <0·0001). This increased use was observed in 12 out of 14 main medication groups, covering most organ systems, and including medications used to treat gastrointestinal, cardiovascular, lung, infectious, neurological, and psychiatric diseases. For these 12 main medication groups, the proportion of users was 1.1- to 1.8-fold higher in the IBD population already ten years prior to IBD diagnosis (p-value <0.0001). The pattern applied across IBD subtypes, sex, and age. The increased use by individuals with IBD became even more pronounced for several medication groups, the closer measurements were to a diagnosis of IBD. The IBD population had a steep increase in use of several medication groups in the two years imminent to diagnosis. Conclusion: There is an increased use of a broad range of medications a decade before diagnosis of IBD. These findings further suggest a long pre-diagnostic phase of IBD, association of IBD with other immune-mediated diseases, and that IBD could be a multiorgan disease to a much larger extent than hitherto established. The long pre-diagnostic period is a window of opportunity for earlier detection, diagnosis, and intervention of IBD.